Exploring Saudi EFL Teachers’ Perceptions of Using Reflective Practice as a Tool for Professional Development - Mastour Alharthi, Rasha; Sultan Althaqafi, Abeer (International Journal of English Language Education, 2023)
This study aimed to investigate the perceptions of male and female English as a Foreign Language (EFL) teachers regarding using reflective practice as a professional development tool and the obstacles that hinder them from adopting reflective practice. To achieve this, a quantitative approach was employed to collect data. A questionnaire with a study sample of 73 teachers was utilized as a research instrument. The findings showed that EFL teachers have positive perceptions towards reflective practice in general and that they believe it is a helpful tool to enhance their professional development. However, it was evident from the data that teachers rarely implemented the reflective tools such as reflective journal, lesson reports, and peer observation. Female EFL teachers were found to be more involved in reflective practice than male teachers. The results also revealed that the biggest obstacle that hinder EFL teachers from utilizing reflective practice was related to the institution fixed policies. Based on these findings, this study provides some implications and recommendation that will hopefully foster Saudi EFL teachers understanding and use of reflective practice.